Complex magnetic order in nickelate slabs. Issue 11 (November 2018) - Hepting, M.; Green, R.; Zhong, Z.; Bluschke, M.; Suyolcu, Y.; Macke, S.; Frano, A.; Catalano, S.; Gibert, M.; Sutarto, R.; He, F.; Cristiani, G.; et al.
Abstract Magnetic ordering phenomena have a profound influence on the macroscopic properties of correlated-electron materials, but their realistic prediction remains a formidable challenge. An archetypical example is the ternary nickel oxide system RNiO3 (R = rare earth), where the period-four magnetic order with proposals of collinear and non-collinear structures and the amplitude of magnetic moments on different Ni sublattices have been subjects of debate for decades1–6 . Here we introduce an elementary model system—NdNiO3 slabs embedded in a non-magnetic NdGaO3 matrix—and use polarized resonant X-ray scattering (RXS) to show that both collinear and non-collinear magnetic structures can be realized, depending on the slab thickness. The crossover between both spin structures is correctly predicted by density functional theory and can be qualitatively understood in a low-energy spin model. We further demonstrate that the amplitude ratio of magnetic moments in neighbouring NiO6 octahedra can be accurately determined by RXS in combination with a correlated double cluster model. Targeted synthesis of model systems with controlled thickness and synergistic application of polarized RXS and ab initio theory thus provide new perspectives for research on complex magnetism, in analogy to two-dimensional materials created by exfoliation7 . Surprising phenomena are known to occur when magnetic systems are confined to low-dimensional geometries. A resonant X-ray scattering study of NdNiO3 slabs reveals a crossover between different magnetic ground states as a function of thickness.